P386 Cancer risk among people with HIV, HBV and/or HCV infections. (14th July 2019) - Darvishian, Maryam; Rossi, Carmine; Wong, Stanley; Yu, Amanda; Wong, Jason; Buxton, Jane; Gilbert, Mark; Binka, Mawuena; Butt, Zahid; Bartlett, Sofia; Pearce, Margo; Alvarez, Maria; et al.
Abstract : Background: HIV, hepatitis B virus (HBV) and hepatitis C virus (HCV) infections each are associated with increased cancer risk. In this study, we assessed the effect of co-occurrence of HIV, HBV and HCV on all cancers, anal cancer, non-Hodgkin Lymphoma (NHL) and liver cancer. Methods: We used the British Columbia Hepatitis Testers Cohort (BC-HTC) which includes all individuals (∼1.7 million) tested for HCV or HIV, or diagnosed with HCV, HIV, or HBV linked with data on cancers. We included individuals tested for all three infections since 1990 and followed them from the date of their last test until the first cancer diagnosis, death, or 12/31/2015. We utilized the Fine and Grey competing risks regression model to estimate adjusted sub-distributional hazard ratios (aHRs) for outcomes, with death as a competing risk. Results: Among 514, 501 individuals tested for all infections, 12, 586 had any cancer (2.45%), 100 had anal cancer (0.02%), 552 had NHL (0.11%), and 1, 081 had liver cancer (0.21%) during a median follow-up of 4.19 years. Compared to no infection, the aHR for all cancers was the highest for HIV/HBV co-infections (HR 2.55, 95% CI: 1.91–3.42) followed by triple infections (aHR 2.29, 95% CI: 1.80–2.89). The risk of anal cancer was higher among individuals with HIV (triple infection aHR 22.61, 95% CI: 7.27–70.33), while risk of the liver cancer was higher among those with HBV or HCV mono or co-infections and triple infections. The risk of NHL was the highest among HIV/HBV co-infections followed by triple infection. Conclusion: HIV, HBV and HCV infections are associated with an overall higher risk of cancer. The highest risks for anal cancer and NHL were among those living with HIV infection. The observed association between HCV and anal cancer, which may be due to the presence of human papillomavirus and/or residual confounding, requires further investigation. Disclosure: No significant relationships.